Pengaruh Kualitas Pelayanan Kualitas Produk dan Persepsi Harga Terhadap Kepuasan Pelanggan di Marawa Beach Club - Andira Nova Winazora; Youmil Abrian; Yuke Permata Lisna (JURNAL KAJIAN PARIWISATA DAN BISNIS PERHOTELAN, 2024)
This research purposes is to analyze the influence of service quality, price, and product quality on customer satisfaction at Marawa Beach Club, Padang, utilizing the SmartPLS method. The research employed a survey with an associative causal approach and quantitative data collection. Data were gathered through a questionnaire distributed to 278 respondents. The data analysis utilized SmartPLS 4, employing the technique of Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicated that service quality has a positive but influence in not significant on satisfaction of customer. Conversely, price and quality of product significantly impact customer satisfaction positively. The implications of these findings suggest that Marawa Beach Club's management can enhance service quality, adjust pricing, and improve product quality to maximize customer satisfaction. This research contributes to understanding the factors affecting customer satisfaction in the tourism industry and serves as a guideline for future research in this field.